Perceived flood risk severity and response efficacy affect migration intentions in flood-prone regions of Klang Valley in Malaysia - Abdullah Al Mamun; Mohammad Masukujjaman; Mahalasmi Radhakrishnan; Mohammad Nurul Hassan Reza; Wan Mohd Hirwani Wan Hussain (Communications Earth & Environment)
Abstract Here, we investigate how the Norm Activation Model and Protection Motivation Theory factors shape migration decisions in response to flood risks. Using a cross-sectional survey and convenience sampling, we collected 345 responses, which were analysed utilizing the Smart-Partial Least Squares software. The findings reveal that awareness of environmental consequences influences the sense of environmental responsibility, as well as perceived severity and vulnerability. In turn, environmental responsibility influences self-efficacy and response efficacy. Furthermore, perceived severity and response efficacy influence the migration intentions, and average household income influences the association between response efficacy and migration intentions. Policymakers should focus on improving community resilience by considering socioeconomic factors and individual experiences in disaster risk management. Our study offers insights into the role of socioeconomic and psychological factors in flood-induced migration and contributes to both theoretical development and policymaking for disaster risk management in flood-prone regions.